The relationship marketing practices of travel agencies in the Western Cape Province - M. Roberts-Lombard; T. F.J. Steyn (South African Journal of Business Management, 2008)
Relationship marketing has received much attention and widespread publicity over the past ten years and has moved to the forefront of research and practice. It provides organizations with a management tool to establish economically profitable relationships, networks and interactions with different, but equally important stakeholder markets. The purpose of the article is to research the relationship marketing practices of travel agencies in the Western Cape province. The empirical research component of the study consisted of the completion of structured questionnaires through personal interviews. The questionnaire consisted of a structured format and incorporated two types of questions, namely closed-ended questions and five point Likert-type statements. The findings of the study concluded that the relationships between travel agencies and the different role players in their market environment are fragmented. The direct marketing initiatives of SAA and hotel groups such as the Southern Sun and Protea hotels are putting strain on the current relationship between travel agencies and these suppliers. The managerial implications for the study specify that an environment must be created which is more accessible to the critical interaction between the travel agency in the Western Cape province and its different role players. This is especially relevant considering that organisations are continuously becoming more aware that their success within a highly competitive market environment depends on the building of long term relationships with each of these role players.
Keywords: 650